Optimization of extraction of antioxidants from lamiaceae sp. by boiling - Muhammad Affiq Saufi, Nordin (2010)
This research is conducted to study the effects of temperature and time of boiling in the extraction of antioxidants from ati-ati (Lamiaceae sp.) plants. In this research, there are two major objectives which are the study of the effect on antioxidants activity of ati-ati (Lamiaceae sp.) plants extraction conducted by repeated boiling and the study of scale up and optimization of the antioxidants extraction from ati-ati (Lamiaceae sp.) plants. In the scale up and optimization study, the experiments were conducted under different levels of two variables of temperature (50, 75 and 100 oC) and time (60, 105 and 150 minutes). In the repeated boiling study, the levels of temperature and time used are at the optimum condition only which are at 100 oC and 150 minutes. The method used to analyze antioxidants levels was 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay. Antioxidants activity assay are based on measurement of the loss of DPPH colour at wavelength of 517 nm monitored via UV-VIS spectrophotometers. The percentage of the DPPH remaining is calculated as % antioxidant activity. In order to determine the optimum condition of the antioxidants activity, several mathematical method were used such as the 22 factorial experiments and using linear regression. In the use of Yates‟ method, the calculation has proved that temperature has contributed to the biggest main effect on antioxidants activity while the interactive effect of temperature and time on antioxidant yield is also significant. For the linear regression method, the coefficients a₁ to a₂ that are obtained from calculation are small compared to the constant a₀. The area investigated is a plateau which may contain the maximum yield of antioxidants activity.